Journal-based Islamic Educational Management Teaching Materials Development for Madrasah Ibtidaiyah Teacher Education Studentsâ€™ - Imron Muttaqin; Rizki Susanto (Al Ibtida: Jurnal Pendidikan Guru MI, 2021)
AbstractThis study aimed to develop the representative material of Islamic education management. The teaching materials using education management theories and thinking were enriched with articles using Mendeley reference management. Modified research and development designs method were used. Data were collected using a Google form. The population and sample were Madrasah Ibtidaiyah Teacher Education (PGMI) IAIN Pontianak students of the academic year 2020/2021. Findings reported that teaching materials developed from online journals have a high level of usefulness and are easy to use. The students can get the latest references published in online journals, making it easier to understand and learn about the course topic. This study suggests that lecturers and students use Mendeley to look for references and write scientific papers.Keywords: Islamic education management, teaching material, scientific journal, mendeley.Â AbstrakPenelitian ini bertujuan untuk mengembangkan materi representatif manajemen pendidikan Islam. Materi ajar yang menggunakan teori dan pemikiran manajemen pendidikan diperkaya dengan artikel dengan menggunakan referensi manajemen Mendeley. Metode penelitian dan pengembangan yang dimodifikasi digunakan. Pengumpulan data menggunakan google form, populasi dan sampel dari mahasiswa Pendidikan Guru Madrasah Ibtiadiyah (PGMI) IAIN Pontianak tahun ajaran 2020/2021. Hasil penelitian dilaporkan bahwa bahan ajar yang dikembangkan dari jurnal online memiliki tingkat kegunaan yang tinggi dan mudah digunakan. Mahasiswa dapat memperoleh referensi terbaru yang telah dipublikasikan di jurnal online, sehingga lebih mudah dipahami dan mudah dipelajari sesuai dengan topik mata kuliah. Penelitian ini menyarankan dosen dan mahasiswa menggunakan Mendeley untuk mencari referensi dan menulis karya ilmiah.Kata kunci: manajemen pendidikan Islam, bahan ajar, jurnal ilmiah, mendeley.